2012
DOI: 10.1177/1352458512438238
|View full text |Cite
|
Sign up to set email alerts
|

Systemic complement profiling in multiple sclerosis as a biomarker of disease state

Abstract: Background:There is increasing evidence of significant and dynamic systemic activation and upregulation of complement in multiple sclerosis (MS), which may contribute to disease pathogenesis.Objective:We aimed to investigate the pathological role of complement in MS and the potential role for complement profiling as a biomarker of MS disease state.Methods:Key components of the classical, alternative and terminal pathways of complement were measured in plasma and cerebrospinal fluid (CSF) of patients with MS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 33 publications
6
88
1
Order By: Relevance
“…In this study, we focused on complement components previously shown to play a role in the pathogenesis of autoimmune brain disease. C3, C4 and C6 have been implicated in EAE, a model for multiple sclerosis [4951]. Moreover, C3 and C4 have been reported to be involved in the pathogenesis of NPSLE [26, 52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on complement components previously shown to play a role in the pathogenesis of autoimmune brain disease. C3, C4 and C6 have been implicated in EAE, a model for multiple sclerosis [4951]. Moreover, C3 and C4 have been reported to be involved in the pathogenesis of NPSLE [26, 52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…This physiological process has also been implicated in pathological synapse elimination in the context of schizophrenia and dementia [37][38][39]. Increased levels of C1q and iC3b (classical complement pathway markers) were reported in human brain samples in focal cortical dysplasia [31], suggesting that aberrant complement activation occurs in patients with drug resistant seizures. Our current study suggests that dysregulation of the classical (C1inh, C4), alternative (FH, properdin, C3) and terminal (TCC) pathways also contribute to epilepsy pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein concentration (µg/ml) was automatically calculated by reference to the standard curve using GraphPad Prism version 5 (La Jolla, CA, USA). Detection limits, working ranges and assay performance were determined as described [31], using serum from local healthy controls.…”
Section: Immunoassaysmentioning
confidence: 99%
“…We previously reported that plasma levels of Bb and TCC were not elevated in MS compared to controls, while C4a was elevated but only in acute relapse. 34,35 These data demonstrate that complement activation represents a fundamental difference between the two diseases; peripheral evidence of complement activation (impacting all pathways) is specific to NMOSD. We concur with the conclusion of Tuzun et al that NMOSD differs from MS "by predominance of complement system involvement".…”
mentioning
confidence: 98%